2022
DOI: 10.1038/s41467-022-31880-6
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes in circulating Tfh cells influence development of functional malaria antibodies in children

Abstract: T-follicular helper (Tfh) cells are key drivers of antibodies that protect from malaria. However, little is known regarding the host and parasite factors that influence Tfh and functional antibody development. Here, we use samples from a large cross-sectional study of children residing in an area of high malaria transmission in Uganda to characterize Tfh cells and functional antibodies to multiple parasites stages. We identify a dramatic re-distribution of the Tfh cell compartment with age that is independent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…Interestingly, females were more likely to be submicroscopic carriers (OR 1.6 (1.3-2.0)) a finding that was also mirrored in Papua, Indonesia, among a population with a similar rate of asymptomatic and submicroscopic infection with a similar odds ratio (adjusted OR = 1.4 (1.0– 1.8)) (Pava et al, 2016). This may be consistent with recent observations that females have higher anti-malaria antibody titers (Chan et al, 2022) and clear asymptomatic infections at a faster rate than males (Briggs et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, females were more likely to be submicroscopic carriers (OR 1.6 (1.3-2.0)) a finding that was also mirrored in Papua, Indonesia, among a population with a similar rate of asymptomatic and submicroscopic infection with a similar odds ratio (adjusted OR = 1.4 (1.0– 1.8)) (Pava et al, 2016). This may be consistent with recent observations that females have higher anti-malaria antibody titers (Chan et al, 2022) and clear asymptomatic infections at a faster rate than males (Briggs et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…(Oyong et al, 2022) One study in Uganda where malaria is holoendemic with seasonal peaks, was able to show that a shift from T H 2-to T H 1-polarized cT FH subsets occurred during the first 6 years of life, and was associated with the development of functional antibodies against Pf-malaria; yet appeared to be independent of malaria exposure as this age-associated shift was also observed in a malaria naïve population. (Chan et al, 2022) Interestingly, this study also found that a higher proportion of T H 17-cT FH cells was associated with a decreased risk of P. falciparum infection the following year, however the authors postulated that this phenomenon could have been driven by previous exposure to the parasite. The observed higher abundance of T H 2-like cT FH cells in children younger than 6 years old and the age-associated increase in T H 1-cT FH cells achieving the same proportion of T H 1-cT FH cells by 6 years of age and into adulthood appeared to be independent of malaria exposure.…”
Section: Introductionmentioning
confidence: 60%
“…A Ugandan study by Chan et al (Chan et al, 2022) demonstrated an age-associated change in cT FH subsets independent of malaria and, thus, supports the importance of accounting for age when evaluating antigen-specific cT FH profiles. Second, our study reveals that adults have a robust cT FH 17-and cT FH 1/17-like subset response to PfGARP but not to PfSEA-1A.…”
Section: Discussionmentioning
confidence: 79%
“…Factors such as age, malaria exposure, and the duration of infection can differentially modulate the expansion of Th1-, Th2-, and Th17-type cTfh cells in response to P. falciparum infection [7,43,44]. First, an early Th2 bias in the cTfh pool is seen at peak parasitemia in experimental human challenge with P. falciparum, followed by a markedly increased proportion of Th1 cTfh cells one week after treatment [7].…”
Section: Discussionmentioning
confidence: 99%